Innovative Behavioral Instrument for Social Impact Assessment: Creating and Evaluating a Measuring Instrument for Stakeholder Engagement in Development Projects Scale - Chotratanakamol, Krisana (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
High-quality behavioral instruments for social impact assessment are still lacking in Thailand. This research aims to create and evaluate the quality of instrument items, explore and confirm the components of the Measuring Instrument, and test the validity of the Stakeholder Engagement in Development Projects scale (SHEP). The sample for this study consisted of 520 stakeholders involved in development projects. The research process comprised four steps. In the process of examining item quality and conducting exploratory factor analysis, the results found that the SHEP measurement model includes 3 components with 15 items, explaining 70.09% of the variance. In the confirmatory factor analysis, the data showed the model was a good fit (χ² = 95.154, df = 75, p = 0.0581, RMSEA = 0.047, CFI = 0.983, TLI = 0.976, SRMR = 0.055). The SHEP scale demonstrated a reliability of 0.92. When testing convergent validity, the SHEP scale was positively correlated with the Social Support in Workplace scale (r = 0.516, p < .01). Additionally, incremental validity testing revealed that the scale could significantly predict increased Work Engagement Behavior (∆F = 14.34, p < .05), with a predictive power increase of 6.6%. The SHEP scale, which demonstrates both validity and reliability, can be confidently employed in social impact assessments and research.